The Potential of Sonication Residue of Hydrilla verticillata Modified with Citric Acid as a Biosorbent for Cadmium Metal - Ahmad Ghanaim Fasya; Dewi Sinta Megawati; Dewi Yuliani; Marsannada Marsannada; Jihan Rizky Wandira; Srikandi Amanda Putri (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
The increase in the number of industries in this era has an impact on water-related environmental problems, particularly heavy-metal waste, including cadmium. This study aims to determine the ability and optimal conditions of the sonication residue biosorbent Hydrilla verticillata. Biosorbents were obtained from sonication residues, then demineralized with 0.4 M HNO3 and modified with 1 M citric acid. Pure and modified biosorbents were subjected to adsorption tests at varying pH levels (5-9), contact times of 15, 30, 45, 60, 75, 90, 105, and 120 minutes, and initial concentrations of 5, 10, 15, 20, and 25 ppm. All adsorption experiments were conducted in triplicate, and the results are presented as mean values. This approach ensures the reliability of the adsorption performance evaluation. The resulting solution was then digested, analyzed using the AAS instrument, and characterized using the FTIR instrument. The results of the research were the successful modification of the biosorbent, marked by a change in color from brownish green to brown and a rough texture, and the detection of the IR spectrum of the C=O group at 1728.21 cm−1. The optimum conditions were obtained with the modified biosorbent: pH 7 (93.6%), contact time 105 minutes (98.3%), and initial concentration 10 ppm (98.7%).